2020
DOI: 10.1016/j.jad.2019.11.161
|View full text |Cite
|
Sign up to set email alerts
|

Is cognitive performance associated with anxiety and depression in first-episode psychosis?

Abstract: Background: In first-episode psychosis (FEP), symptoms of anxiety and depression are common. We examined whether cognitive performance is associated with these clinical measures in FEP during a one-year follow-up. Methods: Young adults with non-affective FEP (n = 52) were assessed two months after their first psychiatric contact for psychosis. Matched controls (n = 62) were administered a baseline assessment. 32 FEP subjects and 44 controls were assessed again at a one-year follow-up. In both assessments, a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Menopause-related estrogen decline also increases the risk of cognitive impairment [42]. This finding is in agreement with those of Lindgren et al [43], who found associations between affective symptoms and poorer cognitive performance, but unlike in our study, the correlations did not reach statistical significance. Similarly, previous studies have shown the association between anxiety and depression with cognitive performance in the general population [44,45], with some pathology such as Parkinson's [46].…”
Section: Discussionsupporting
confidence: 91%
“…Menopause-related estrogen decline also increases the risk of cognitive impairment [42]. This finding is in agreement with those of Lindgren et al [43], who found associations between affective symptoms and poorer cognitive performance, but unlike in our study, the correlations did not reach statistical significance. Similarly, previous studies have shown the association between anxiety and depression with cognitive performance in the general population [44,45], with some pathology such as Parkinson's [46].…”
Section: Discussionsupporting
confidence: 91%
“…Generally, affective symptoms in FEP may associate with a more severe clinical picture (70). Our previous results suggest that affective symptoms right after getting ill may associate with better cognitive performance (26) as well as with a better functional 1-year outcome (27), which possibly relates to better insight into the situation that evokes negative emotions and a better understanding of the situation. Positive symptoms of psychosis are seldom associated with cognitive functioning (54), and they also seem to interfere with everyday functioning less than negative symptoms (21).…”
Section: Discussionmentioning
confidence: 91%
“…Affective symptoms in psychotic disorders may also be linked to poorer cognition (22)(23)(24), but in some studies, the direction of the association has also been the reverse (25). We have previously found higher affective symptoms to associate with better cognitive performance right after getting ill (26) and with a better functional 1-year outcome in FEP (27), suggesting that anxiety and depression do not necessarily signal a poor prognosis in FEP.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies suggest that anxiety has a negative impact on the severity of positive and negative symptoms, social and overall function and global quality of life (Braga, Mendlowicz, Marrocos, & Figueira, 2005;Huppert, Weiss, Lim, Pratt, & Smith, 2001;Karpov et al, 2017;McEnery et al, 2019;Pallanti, Quercioli, & Hollander, 2004).On the other hand, higher anxiety has been associated with better treatment-decision capacity and insight (Larkin & Hutton, 2017;Wiffen, Rabinowitz, Lex, & David, 2010). We have previously found that anxiety in FEP associate with higher cognitive performance at the early stage of illness but not at 12 months (Lindgren, Birling, & Kieseppä, 2020). However, the potential significance of anxiety in predicting remission and long-term functioning in FEP has rarely been studied.…”
Section: Introductionmentioning
confidence: 77%